Analysis of tympanosclerotic plaques via atomic force microscope and scanning electron microscope - Aslan, Hale; Sinan Başoğlu, Mehmet; Ekber İlknur, Ali; Özbay, Can; Eren, Erdem; Oğuz Kılıç, Duygu; Kulduk, Erkan; Katılmış, Hüseyin (ENT Updates, 2012)
Objective: To present new information to the literature by imaging the calcospherule forming tympanosclerotic plaque's structure with atomic force microscope and to analyze the elementary structure of it with energy dispersive X-ray detector adapted to the scanning electron microscope. Methods: Samples taken from 30 patients who underwent surgery for tympanosclerosis were retrospectively evaluated in our tertiary referral center. The surface topography and three-dimensional images of the hardest plaque was analyzed using atomic force microscopy and examined elemental composition of 5 different calcospherule in 5 different plaques using scanning electron microscopy energy dispersive X-ray spectroscopy. Results: In all sides of study, the rate of fronto-ethmoidal cell was 20.9%. When cases with sinonasal signs (group II and III) and control group (group I) were compared, intersiThree-dimensional analysis of the tympanosclerotic plaque using atomic force microscopy showed calcium phosphate crystalline structures. Scanning electron microscopy with energy dispersive X-ray spectroscopy was used to quantify the calcium, phosphate, carbon, nitrogen, oxygen, sodium, and magnesium present. Conclusion: We believe that knowledge of the surface topography and elemental composition of tympanosclerotic plaque will contribute to understanding the etiology of tympanosclerosis and its treatment.